99mTechnetium-Unithiol Complex, a New Pharmaceutical for Kidney Scintigraphy - Liniecki, J.; Surma, M.; Mlodkowska, E.; Ogiński, M. (Nuklearmedizin - NuclearMedicine, 1977)
Dynamic kidney scintigraphy was performed in 8 patients after administration of 197Hg-chlormerodrin or of a new complex: 99mTc-Unithiol. Kinetics of image formation and goodness of kidney imaging were studied both quantitatively and qualitatively. The results demonstrated that 1½–3 hrs after i.v. administration of either compound equally good kidney scintigrams may be obtained. Clinical experience on more than 300 patients supports this conclusion.